Rancang Bangun Sistem Layanan Pre-Order Produk UMKM Kain Tenun Berbasis Web untuk Meningkatkan Penjualan dengan Metode Prototype (Studi Kasus: Vanny Situmeang Ulos Tarutung) - Ruth Abelia Purba; Ricky Ramadhan Harahap; Rahmadani (CV. Hawari, 2026)
Micro, Small, and Medium Enterprises (MSMEs) producing ulos woven fabrics play an important role in cultural preservation as well as community economic development. However, at Vanny Situmeang Ulos Tarutung MSME, product orders are still carried out through direct conversations or short messages, resulting in poorly documented order records, difficulty in tracking orders, and potential errors. In addition, customers experience difficulties in obtaining product information and monitoring order progress. This condition also limits the marketing reach of the products. This study aims to provide a web-based pre-order service for ulos woven fabric products that can assist order management, facilitate customers in placing orders, and expand marketing coverage. The method used is the prototype method, which involves creating an initial model based on user requirements, followed by evaluation and refinement until the final result is achieved. Research data were obtained through observation and interviews with the MSME owner. The results show that the web-based pre-order service is able to store order data in an organized manner, facilitate order management by the MSME, and provide convenience for customers in accessing product information and placing orders. Furthermore, the web platform enables the products to reach a wider audience, thereby increasing sales potential. Therefore, the developed service can support the sustainable growth of ulos woven fabric MSMEs.